2004
DOI: 10.1086/382582
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Solar Type I Continuum Noise Storm in the 50–80 MHz Band and Plasma Characteristics in the Associated Source Region

Abstract: Continuum observations of a solar noise storm in the frequency range of 50 -80 MHz observed with the Gauribidanur radio spectrograph during 2000 September, 26 & 27, are presented here. The radio spectral index of the noise storm continuum in the band 50 -80 MHz is found to be ≈ 3.65 during the above period. The Noise Storm continuum radiation is explained as a consequence of the non-thermal, plasma emission mechanism. The beam-density of suprathermal electrons is estimated for the coronal plasma near the sourc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The detailed multifrequency characteristics of noise storms have not been studied very well; to the best of our knowledge, the only such study after the early pioneering study of Smerd [7] have been those of Thejappa & Kundu [13], Kundu & Gopalswamy [12] and Sundaram & Subramanian [6]. While Smerd's [7] early results showed that noise storms tended to be brightest around 100 MHz, with intensities tapering off on either side of this (approximate) frequency, Sundaram & Subramanian's [6] more recent, relatively sophisticated studies were confined only to the 50-80 MHz frequency range, and showed that noise storm intensities clearly rose as a function of frequency in this range. We will have occasion to comment on the interesting implications of such multifrequency observations in § 6.…”
Section: Observations Of Noise Storm Emission 21 Multifrequency Obser...mentioning
confidence: 99%
“…The detailed multifrequency characteristics of noise storms have not been studied very well; to the best of our knowledge, the only such study after the early pioneering study of Smerd [7] have been those of Thejappa & Kundu [13], Kundu & Gopalswamy [12] and Sundaram & Subramanian [6]. While Smerd's [7] early results showed that noise storms tended to be brightest around 100 MHz, with intensities tapering off on either side of this (approximate) frequency, Sundaram & Subramanian's [6] more recent, relatively sophisticated studies were confined only to the 50-80 MHz frequency range, and showed that noise storm intensities clearly rose as a function of frequency in this range. We will have occasion to comment on the interesting implications of such multifrequency observations in § 6.…”
Section: Observations Of Noise Storm Emission 21 Multifrequency Obser...mentioning
confidence: 99%
“…The bursts are considered to be evidence of successive electron accelerations which, unlike the transient acceleration associated with flares, continue for hours or days. It is now generally accepted that the radiation is fundamental (F) plasma emission (Shanmugha Sundaram & Subramanian 2004) due to the coupling of Langmuir and low-frequency waves (either lower-hybrid or ion-acoustic), and the observed circular polarization results from propagation effects in the presence of a magnetic field. The type I bursts primarily relate to non-flaring sunspot active regions and point to an exceedingly restless corona even during non-flaring times.…”
Section: Introductionmentioning
confidence: 99%
“…Applying the standard expressions for the group velocity (v g ) and Landau damping constant (γ L (≡ τ −1 )) , (Thejappa, Gopalswamy & Kundu 1990;Thejappa 1991;Shanmugha Sundaram & Subramanian 2004), and assuming values for the phase velocity [v ph (≈ v T b )] to be 10 10 cm s −1 and v T ≈ 3.89 × 10 8 cm s −1 , the estimated damping length ( r) is ∼1.1 × 10 −2 R . v ph ≈ v T b , when critical fluctuations in T eff of the L waves, at the threshold densities of the trapped electrons that lie proximal to the onset of plasma instabilities, rise steeply to the levels of T b observed for Type I burst events.…”
Section: Time-profile Analysis: Distribution Of Lifetimes Of Isolatedmentioning
confidence: 99%
“…Applying the standard expressions for group-velocity (vg) and Landau damping constant (γL (≡ τ −1 )) , (Sundaram & Subramanian 2004;Thejappa 1991;Thejappa, Gopalswamy, & Kundu 1990), and assuming values for the phase velocity (v ph (≈ vT b )) to be 10 10 cm s −1 and vT ≈ 3.89 . 10 8 cm s −1 , the estimated damping-length (∆r) is ∼ 1.1 × 10 −2 R⊙.…”
Section: Distribution Of Lifetimes Of Isolated Burstsmentioning
confidence: 99%